PEMODELAN SOLAR TRACKER DENGAN PENGENDALI PI, PD, DAN PID MENGGUNAKAN MATLAB-SIMULINK DENGAN BEBAN BATERAI - Maharani, Putri; Adam, Ahmad Antares; Mukhlis, Baso; Arifin, Yusnaini; Amin, Nurhani; Mardiansyah, Mardiansyah (Foristek, 2024)
A solar tracker is a photovoltaic (PV) system support tool aimed at optimizing solar energy absorption by directing solar cells to follow the movement of the sun.In this research, a solar tracker for PV with battery load model was created using MATLAB-Simulink with each controller, namely Proportional Integral (PI), Proportional Derivative (PD) and Proportional Integral Derivative (PID) and the simulation results were compared. The simulation results show that the PID controller is the controller with the most optimal results because all set point values ​​entered in the output remain the same and the overshoot value is also low, the PD controller is the controller that produces high errors and also overshot reaching 120 V, and the PI controller is the controller that the results are closest to a PID controller where the resulting overshoot value is only around 20%.